Gastrointestinal and Hepatological Manifestations in Severe Acute Respiratory Syndrome Coronavirus 2 Infection: Results from the Major COVID Hospital in Serbia - Dragana Mijac; Samir Vucelj; Kristina Todorovic; Marko Vojnovic; Biljana Milicic; Snezana Lukic; Branka Filipovic; Marija Marjanovic Haljilji; Dusan Popovic; Tatjana Adzic Vukicevic (Microorganisms, 2023)
The coronavirus disease of 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), includes a clinical spectrum of diseases from mild to severe progressive pneumonia, which has affected and still affects the human population worldwide. Most commonly, it is presented by respiratory symptoms, but studies have shown that about 50% of patients with SARS-CoV-2 infection have at least one gastrointestinal symptom (GI), predominantly nausea, diarrhea, vomiting, or loss of appetite. In addition, abnormal liver functional tests are commonly present in the SARS-CoV-2 virus. The aim of our study was to examine the GI and hepatic manifestations of COVID-19 in patients hospitalized due to COVID-19 pneumonia in “COVID hospital Batajnica”, University Clinical Center of Serbia in Belgrade. The study included 498 consecutive patients, and the data was obtained from the patient’s electronic medical history. GI symptoms included nausea, vomiting, diarrhea, and anorexia. Collected laboratory values included baseline and peak values of blood count, inflammatory parameters, liver function tests, renal function tests, and cardiac enzyme tests. The results have shown that GI symptoms occurred in 26% of cases at diagnosis, which indicates the great susceptibility of the GI system to SARS-CoV-2. There was a high risk of liver injury in patients with COVID-19 pneumonia (>60%). The level of AST is more often increased compared to ALT, which is different from other virus-induced liver lesions and may be a useful indicator of SARS-CoV-2 infection. Further research should focus on the causes of liver damage in SARS-CoV-2 virus and the impact on treatment and outcome of COVID-19 disease.